Biblioteka kościoła parafialnego w Szadku w drugiej poł. XVIII w. - Rulka, Ks. Kazimerz (Biuletyn Szadkowski, 2011)
The library of the parish church in Szadek – being the seat of Szadek Decanate and belonging in 1818 to Gniezno Archdiocese – was referred to, with listings of all the books that it contained, in parish documents (canonical visitations of the parish) of 1762, 1779 and 1788. It was mainly used by local priests. After less than half a century of existence, it was destroyed, probably in a church fire in 1802. The registers list some 35 books, most likely in printed form. The themes of this collection of books point to it being the property of one of the parish priests, donated after his death to the parish. Nearly half of the books are works useful in preaching: collections of sermons and examples. The remaining publications, too, are intended to help priests in their pastoral work, religious instruction and preaching. Among Polish parish libraries of the 18th century, this collection falls within the category of small libraries (1–50 books).